Modern Solutions for the Prevention and Diagnosis of Multiple Sclerosis - oʻgʻli, Qurbonov Jo’rabek Sultonmurod; Arzikulovich, Kadirov Umid; Ziyadulloyevna, Khakimova Sokhiba (American Journal of Bioscience and Clinical Integrity, 2025)
Multiple sclerosis is a chronic disease in which the immune system, which normally protects against pathogens (e.g., viruses, bacteria, fungi), mistakenly attacks and destroys the myelin sheath of neurons in the brain and spinal cord. The myelin sheath helps neurons transmit impulses quickly and correctly. If it is damaged, the impulse is transmitted incorrectly. As a result, important body functions controlled by the central nervous system (CNS) can be impaired: vision, speech, muscle tone, thinking, urination, defecation.